1968
DOI: 10.1126/science.160.3834.1335
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Isotope Analysis of Recent Tropical Pacific Benthonic Foraminifera

Abstract: Analysis by the oxygen-isotope method of samples of benthonic Foraminifera, collected at different depths on the continental shelf and slope of western Cenitral America, yielded isotopic temperatures agreeing closely with the temperatures measured in the field. The validity of the oxygen-isotope method as a means of analysis of paleotemperatures is further supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The dissolution process of the host organism could modify the chemistry of the ambient seawater in a limited area around the foraminifera (Toyofuku et al, 2017), although this process is hard to imagine in an environment (cold-water coral reef) that relies on constant water movement to provide nutrients to the main inhabitants (Mienis et al, 2007). As such, we suggest it is more likely that the dissolved material is transported through the cytoplasm to the calcification site (Spero, 1988;Erez, 2003), although further work is required to confirm this.…”
Section: Mixing Modelmentioning
confidence: 84%
“…The dissolution process of the host organism could modify the chemistry of the ambient seawater in a limited area around the foraminifera (Toyofuku et al, 2017), although this process is hard to imagine in an environment (cold-water coral reef) that relies on constant water movement to provide nutrients to the main inhabitants (Mienis et al, 2007). As such, we suggest it is more likely that the dissolved material is transported through the cytoplasm to the calcification site (Spero, 1988;Erez, 2003), although further work is required to confirm this.…”
Section: Mixing Modelmentioning
confidence: 84%
“…Many of the species showing a tendency toward isotopic equilibrium occupy the oxygen minimum layers of the eastern Pacific (Smith and Emiliani, 1968;Dunbar and Wefer, 1984;Grossman, 1984a) and the eastem Atlantic (Ganssen, 1983), including many buliminaceans. Perhaps the same traits that enable species to inhabit inhospitable low oxygen environments also bring about equilibrium precipitation of tests.…”
Section: Vital Effect and Foraminiferal Ecologymentioning
confidence: 99%
“…A large number of publications on Cenozoic palaeoclimates and palaeoceanography using stable isotopic data on foraminifers have appeared, but whether foraminifers secrete the test in equilibrium with the ambient sea-water has not yet been resolved. Various observations suggest deposition in equilibrium (Smith &Emiliani 1968) to near equilibrium (Savin et al 1975;Berger et al 1981) and out of equilibrium (Vinot-Bertouille & Duplessy 1973;Erez 1978). Studies on Recent larger foraminifers have shown that the oxygen isotopic ratios are either close to expected equilibrium values (Luz et al 1983), or, despite the biological fractionation, they are chiefly the function of surface-water temperatures and record the seasonal variations (Wefer & Berger 1980;Wefer et al 1981).…”
Section: Limitationsmentioning
confidence: 97%